EMPIRICAL ANALYSIS OF CROP INSURANCE IN HARYANA STATE BY CUMULATIVE ANNUAL GROWTH APPROACH - Kaur, Satwinder (International Journal of Psychosocial Rehabilitation, 2020)
Dynamic Agriculture is backbone of Indian economy which contributes about 14.00 percent to GDP as well as gives work to 57.00 percent of populace. The development of this division is a fundamental essential for comprehensive development just as decrease of neediness in India. In any case, Indian agribusiness experiences bunch issues and one of them is exorbitant hazard and vulnerability looked by the ranchers. For farming advancement, legislature of India executed different projects and ventures agribusiness subject to rainstorm which is constantly adaptable. It prompts working danger in development of various yields. Regular cataclysms may influence on the yield from farming area. To cover the hazard which may happen in future, there is have to some arrangement and yield protection is just instrument accessible to shield against creation chance in horticulture.